(untitled) (Journal of Pharma Insights and Research, 2025)
Alzheimer’s disease (AD) represents a progressive neurodegenerative disorder that primarily affects memory, language, and visuospatial abilities, with aging as the predominant risk factor. Currently affecting approximately 40 million individuals globally, AD prevalence is projected to increase substantially by 2050. While genetic mutations account for a small percentage of cases (familial AD), most cases are sporadic with multifactorial origins encompassing genetic, environmental, and lifestyle components. The neuropathological hallmarks include amyloid β plaques, tau neurofibrillary tangles, mitochondrial dysfunction, and synaptic deficits. Clinical diagnosis achieves high accuracy when established criteria are properly implemented, though effective treatments remain limited. Recent evidence points to several modifiable risk factors influencing AD onset and progression, particularly in late-onset cases. Psychosocial elements, including social engagement, cognitive stimulation through bilingualism, and emotional wellbeing, demonstrate protective effects. Pre-existing conditions like diabetes, hypertension, dyslipidemia, and obesity significantly increase risk through vascular mechanisms. Lifestyle factors such as physical inactivity, poor dietary habits, sleep disruption, alcohol consumption, smoking, and inadequate oral health further contribute to risk elevation. Prevention strategies emphasize managing vascular and metabolic conditions, promoting physical activity, adherence to beneficial dietary patterns, and addressing psychological health. Nutritional factors, particularly vitamins B6, B12, D, E, and folate, may influence AD development through oxidative stress and homocysteine pathways. Multi-domain interventions targeting these modifiable factors offer promising approaches to delay onset and reduce disease burden